BIG DATA ANALYTICS UNTUK MENDUKUNG PENGAMBILAN KEPUTUSAN PEMASARAN DIGITAL - Martha Gracia; Metta Dwi Arhamarra (Jurnal Riset Multidisiplin Edukasi, 2026)
Big Data Analytics has become a critical instrument in enhancing the quality of decision-making within digital marketing environments. This study examines how the integration of large-scale data processing, predictive modeling, and real-time analytics can support organizations in understanding consumer behavior, optimizing marketing strategies, and improving campaign performance. Through an analysis of relevant literature and industry practices, the research highlights the role of data-driven insights in segmenting markets more accurately, personalizing customer experiences, and identifying emerging trends that influence purchasing decisions. The findings indicate that companies that adopt Big Data Analytics are better equipped to make timely and precise marketing decisions, leading to increased competitiveness, improved return on investment, and stronger customer engagement. This study concludes that the strategic use of Big Data Analytics is essential for organizations seeking sustainable growth in an increasingly dynamic digital marketplace.